Profitability, Liquidity, And Stock Volatility As Determinants Of Firm Value In The Coal Sector Period 2019-2023: - - Wati, Ria Sintya; Utami, Datien Eriska (Al Tijarah, 2024)
This study analyzes the effect of profitability, liquidity, and stock price volatility on firm value in coal issuers listed on the Indonesia Stock Exchange (IDX) and indexed in the Indonesian Sharia Stock Index (ISSI) for the period 2019-2023. Profitability is measured by Return on Assets (ROA), liquidity is measured by Current Ratio (CR), and stock price volatility is measured by Standard Deviation of Stock Returns (STDV), while firm value is proxied by Price to Book Value (PBV).Secondary data were obtained from annual financial reports and analyzed using panel data linear regression with the Fixed Effect Model method. The study's findings suggest that profitability (ROA) and liquidity (CR) have a positive and significant effect on firm value, indicating that companies with high profitability and adequate liquidity tend to have higher market valuations.Conversely, stock price volatility (STDV) has a substantial negative effect on firm value, indicating that high stock price volatility increases investment risk and reduces investor confidence. The findings of this study offer valuable insights for financial managers and investors, guiding their efforts to enhance firm value by managing internal factors and taking into account market risks.